Web Application Development of Community Products for Participative Management to Chaloem Phra Kiat Coconut Shell Handicraft Center in Nakhon Si Thammarat Province. - buangam, pornsin; Sriyom, Utumporn (Business Administration and Management Journal Review, 2023)
This study aims to 1) design and develop for manage and public relations participatory community products a case study of Chaloem Phra Kiat coconut shell handicraft center in Nakhon Si Thammarat province, 2) evaluate the web application quality and satisfaction of user. The researcher determined the size of sample used for the 220 persons; sample of Chaloem Phra Kiat coconut shell handicraft center member 10 persons and 10 web application’ experts selected by purposive, and 200 users selected by accidental. The research tools were included 1) web application for manage and public relations participatory community products 2) evaluate forms, and 3) questionnaires. The data was analyzed by mean and standard deviation. The research results as follows: 1) design and develop for manage and public relations participatory community products view product data, product detail on web browser, easiest, convenient and fast 2) the result web application quality by data’ experts were a high level ( = 3.97, SD. = 0.56) And 3) The users who answer the questionnaires on the web application were a good level ( = 4.30, SD. = 0.75)